The application of financing and dividend decision techniques in practice among Ghanaian chief financial officers (CFOs) - Anthony Owusu-Ansah; Nene Lartey Addico; Godfred Amewu (Cogent Business & Management, 2023)
We use a survey approach to investigate how managers in a frontier market apply financing and dividend decision techniques in practice. 15 firm characteristics were grouped into paired subgroups for a two-sample t-test analysis that generated statistical differences, economic significance levels and ranking for each technique investigated. The Ghanaian listed firm's sample choice was due to the country's persistent volatile macroeconomic environment. In managing the capital structure, managers consider most relevant issuing of stock to give investors a better impression of their firms' prospects (signalling). In choosing between short and long-term debt techniques, the most applied technique is matching the firm's debt maturity with the assets' useful life span. Managers are most concerned about the volatility of their earnings and cash flows on the appropriate amount of debt to use. A probe into debt policy indicates that the most valuable technique is issuing debt when the firm's internal funds are inadequate. Under dividend policy, the most treasured technique is ensuring cash availability which deviated from existing literature. These results show that managers in frontier markets are cash-focused, which may lead to short-termism, which may be non-value-adding but important for survival in their persistent liquidity crunch markets.
Keywords: G30; G35; G31; G39; 650; survey; capital structure; dividend policy; financing decision; CFOs; debt policy